Medical Supply Chain Under Emergency Case - Hiatt, Brian; Hong, Seock-Jin; Kwon, Ik-Whan G.; Kim, Sung-Ho (British Journal of Healthcare and Medical Research, 2023)
Medical supply chain under emergency has been rarely explored. Pandemic, political conflicts, natural disasters, etc. create human sufferings. Healthcare supply chain is inadequate in dealing with such unique set of circumstances. Medical supply chain under emergency often assumes humanitarian responsibilities with emphasis on reliving human suffering. Medical supplies and logistics assets become the most critical components in medical supply chain. Yet, these two critical areas have not been adequately addressed under the healthcare supply chain.